THE IMPLEMENTATION OF DIGITAL MARKETING AT GUCI FARM MSME IN FACING OPPORTUNITIES AND CHALLENGES IN TUNCUNG VILLAGE, MAIWA SUBDISTRICT, ENREKANG REGENCY - Muhammad Aswar Arman; Muhammad Rusdi; Haslindah Haslindah; Inna Mutmainna Cahyani Thahir (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study aims to examine how Guci Farm MSME, engaged in broiler chicken farming, utilizes digital marketing to address opportunities and challenges in Tuncung Village, Maiwa Subdistrict, and Enrekang Regency. The business still relies on traditional promotion methods, limiting its market reach. Using a qualitative approach, data were collected through interviews, observations, and documentation. Findings indicate that social media, especially Facebook, offers strong potential to increase product exposure and customer engagement. Guci Farm benefits from product quality and customer trust but faces challenges such as limited technology, lack of digital marketing knowledge, and absence of a structured promotional strategy. Based on SWOT analysis and the marketing mix (4P), digital marketing can improve promotional effectiveness if supported by proper training, mentoring, and infrastructure. This study suggests the need for collaboration between business actors and external stakeholders to support the sustainable digital transformation of MSMEs. Keywords: Guci Farm; Digital Marketing; MSMEs; Opportunities and Challenges